Modelización económica forestal en Mesopotamia Sur - Olemberg, Demián Jeremías; Vera, Luis Maria; Flores Palenzona, Mario Horacio; De La Peña, Carlos Alberto (EEA Concordia, INTA, 2025)
Publicado en la Revista de las Jornadas Forestales de Entre Ríos